Vulnerability and Young People : Care and Social Control in Policy and Practice - Brown, Kate, 1980- (Book collections on Project MUSE., 2017)
The identification and management of vulnerability has come to play an important role in welfare and criminal justice processes, yet the rising popularity of the notion has largely escaped scrutiny. This book brings together powerful lived realities of vulnerability with academic and practical applications of the concept, exploring the implications of a 'vulnerability zeitgeist' in policy and practice.